2013
DOI: 10.1002/suco.201200028
|View full text |Cite
|
Sign up to set email alerts
|

Design for punching of prestressed concrete slabs

Abstract: Prestressing in flat slabs helps to control deformations and cracking under service loads and allows the required slab thickness to be reduced, thus leading to more slender structures and an economic solution for long spans. However, as a consequence of the limited thickness of these members, punching typically governs at the ultimate limit state. Studies of the punching shear strength have shown that the presence of prestressing in flat slabs has a number of potential beneficial effects, namely the vertical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…This indicates that the increase in the prestressing level from 0.5 to 1.0 MPa can improve the ultimate capacity (16.5%) more effectively than the increase in the prestressing level from 1.0 to 2.0 MPa (10.6%). This is in agreement with Hwang et al (2010) and Clement et al (2013) who concluded that the ultimate capacity is not increased proportionally with the initial prestressing level. The positive influence of the prestressing level tended to reduce with the increase in the initial prestressing level.…”
Section: Effect Of Prestressing Levelsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the increase in the prestressing level from 0.5 to 1.0 MPa can improve the ultimate capacity (16.5%) more effectively than the increase in the prestressing level from 1.0 to 2.0 MPa (10.6%). This is in agreement with Hwang et al (2010) and Clement et al (2013) who concluded that the ultimate capacity is not increased proportionally with the initial prestressing level. The positive influence of the prestressing level tended to reduce with the increase in the initial prestressing level.…”
Section: Effect Of Prestressing Levelsupporting
confidence: 93%
“…The most common failure mode is the punching shear. Many researchers (Higashiyama and Matsui 1998;Hamada et al 2008;Muttoni et al 2012;Clement et al 2013) have proposed the equation to predict the punching shear capacities. Significant work was also performed by Mander et al (2011) to investigate the full-depth precast concrete bridge deck cantilevers, which failed in a flexural and shear mixed failure at the panel-to-panel connection.…”
Section: Introductionmentioning
confidence: 99%
“…The same approach has also been adopted in fib Model Code 2010 to account for the contribution of steel fibres to punching shear strength [26]. Further, application to prestressed slabs [27,28], post-installed shear reinforcement [29] or non-axis-symmetric slabs [30,31] can be found elsewhere.…”
Section: Failure Criterionmentioning
confidence: 99%
“…With reference to the influence of an axial compression r n in the control perimeter, it can be taken into account by replacing the rotation w with a modified rotation w 0 = w + 45r n /E c P 0 as shown in [11]. The load-rotation curve may be calculated with several levels of approximation [4] and it may also include the influence of slab continuity [12], normal forces and applied moments [11,13]. The general approach of the Critical Shear Crack Theory can also be used to treat slabs with irregular column layout and uneven loading [14] as well as punching of rectangular columns [15].…”
Section: Punching Of Flat Slabsmentioning
confidence: 99%